Three trithiadiazepines and a trithiatriazepine. Issue 1 (15th January 2014) - Jones, Ray
<x xml:space="preserve">Abstract</x> The structures of 6‐nitro‐1, 3λ4δ2, 5, 2, 4‐trithiadiazepine [C2HN3O2S3, (1)], 6, 7‐dinitro‐1, 3λ4δ2, 5, 2, 4‐trithiadiazepine [C2N4O4S3, (2)], 1, 3λ4δ2, 5, 2, 4‐trithiadiazepine‐6, 7‐dicarbonitrile [C4N4S3, (3)] and 7‐acetyl‐1, 3λ4δ2, 5, 2, 4, 6‐trithiatriazepine [C3H3N3OS3, (4)] presented here include the most precise determinations of these seven‐membered 10 π‐electron aromatic ring systems published to date. Both (2) and (3) are sited around crystallographic twofold axes with half a molecule per asymmetric unit. Comparison with other published derivatives of these rings reveals the effect of substituents on bonding, conformations and intermolecular interactions, including π‐stacking. The deformation density analysis of (2) is consistent with the expected bonding electron density from other theoretical and experimental studies.